KARAKTERISTIK PAPAN SANDWICH DENGAN INTI PAPAN PARTIKEL - Ignasia Maria Sulastiningsih; Dian Anggraini Indrawan; Jamal Balfas (BRIN Publishing, 2020)
Bamboo has been recoqnized as wood substitute materials by convertting them into engineered bamboo products. Toincrease bamboo utilization efficiency, the waste generated from bamboo processing can be used further as raw materialsfor particleboard manufacture. Besides to get relatively thick and strong material, the bamboo particleboard can beused as a core layer for sandwich panel. The objective of this research was to determine characteristics of sandwichpanel with particleboard as the core layer. There were four types of particleboard used as the core layer of sandwichpanel i.e bamboo particleboard with density of 0.45 g/cm3(A1) and 0.55 g/cm3(A2), and the mixture of bamboojabon particleboards with density of 0.45 g/cm3(A3) and 0.55 g/cm3(A4). There were three types of outer layerof sandwich panel i.e. bamboo strips (B1), jabon plywood (B2), and mahoni plywood (B3). Sandwich panels wereproduced using urea formaldehyde adhesive. The results showed that bamboo-jabon particleboard used as core layerproduced stronger sandwich panels than those using only bamboo particleboards. Bamboo strips as the outer layerproduced stronger sandwich panels than those of using mahoni and jabon plywood. All sandwich panels produced inthis research conform to both the Indonesian Standard and the Japanese Standard requirements for particleboard withveneer overlay.